(untitled) (Applied Biological Research, 2024)
Plant disease management presently relies heavily on chemical fungicides. However, their harmful impact on human and ecosystem, and development of fungicide-resistant strains has emphasized on biological control as alternative eco-friendly strategy for disease management and sustainable agriculture. Trichoderma is a widely used as biocontrol agent against various phyto pathogenic fungi owing to its effective strategies to suppress plant pathogens. The control phenomenon involves direct mechanisms like mycoparasitism, secretion of hydrolytic enzymes which degrade the cell walls of pathogenic fungi, and indirect mechanisms like competition for resources, induction of plant defense mechanism and antibiosis. Trichoderma’s multifaceted approach to biological control makes it environment-friendly option for managing plant diseases. Recent biotechnological approaches have simplified the isolation and characterization of efficient biocontrol agents, along with the identification of their genetic by-products. These techniques facilitate the cloning of these microbes in plants, with aim to bolster their resistance to both biotic and abiotic stresses. Biotechnological advances have not only reinforced the symbiotic interaction between microbes and plants but also allowed the modification of processes through microbial biocontrol agents (MCBAs). Genome sequencing of MBCAs has provided valuable insights into their genetic makeup, aiding their characterization. The present comprehensive review provides an insight to the existing and recent molecular advances utilized to enhance the efficiency of MBCAs in managing plant diseases and understanding biocontrol mechanisms through various omics technologies.